Decentralization in Colombia: reality or mirage? Considerations on the current process - Jorge Enrique Asela Molina (Revista CEA, 2015)
In this article we will try to explain, as a first objective, the decentralized model from a purely theoretical point of view, considered from the contributions of different authors of economic theory, with special emphasis on the progress of political and economic aspects, concerning the management of the Estate. The second objective of this paper is to take a closer look of the decentralization process in Colombia, starting with the Constitution of 1991, some of its achievements, setbacks and current challenges. Finally, this paper will briefly discuss how much local authorities depend on the funds allocated via transfers done by the Estate, this will be done through the measure description intergovernmental dependence proposed by DNP.